2021
DOI: 10.1051/0004-6361/202140957
|View full text |Cite
|
Sign up to set email alerts
|

Creep tide model for the three-body problem

Abstract: We present a tidal model for treating the rotational evolution in the general three-body problem with arbitrary viscosities, in which all the masses are considered to be extended and all the tidal interactions between pairs are taken into account. Based on the creep tide theory, we present a set of differential equations that describes the rotational evolution of each body, in a formalism that is easily extensible to the N tidally interacting body problem. We apply our model to the case of a circumbinary plane… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…In the framework of the constant time lag (CTL) model (e.g., Mignard 1979), we have been investigating the tidal evolution of CB planets with the 3BP, and found results remarkably different from those obtained with the 2BP approach (e.g., Correia et al 2016). For example, regarding the spin evolution, we found different pseudo-synchronous stationary states, which may even be subsynchronous for low-eccentricity CB planets (Zoppetti et al 2019(Zoppetti et al , 2020. Moreover, according to our model the orbital evolution is perhaps even more interesting.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…In the framework of the constant time lag (CTL) model (e.g., Mignard 1979), we have been investigating the tidal evolution of CB planets with the 3BP, and found results remarkably different from those obtained with the 2BP approach (e.g., Correia et al 2016). For example, regarding the spin evolution, we found different pseudo-synchronous stationary states, which may even be subsynchronous for low-eccentricity CB planets (Zoppetti et al 2019(Zoppetti et al , 2020. Moreover, according to our model the orbital evolution is perhaps even more interesting.…”
Section: Introductionmentioning
confidence: 81%
“…In Zoppetti et al (2019Zoppetti et al ( , 2020, we used the CTL model and found that for Kepler-like CB systems the characteristic tidal timescales of the planetary rotational evolution are typically much lower than those associated with the orbital evolution. Thus, CB planets are expected to have a significant orbital evolution only after reaching rotational stationary states.…”
Section: Tidal Forces On the Planetmentioning
confidence: 99%
See 3 more Smart Citations